Mitigation of agriculture emissions in the tropics: comparing forest land-sparing options at the national level - Carter, S.; Herold, Martin; Rufino, Mariana C.; Neumann, K.; Kooistra, L.; Verchot, Louis V. (Copernicus GmbH, 2015)
Abstract. Emissions from agriculture-driven deforestation are of global concern, but forest land-sparing interventions such as agricultural intensification and utilization of available non-forest land offer opportunities for mitigation. In many tropical countries, where agriculture is the major driver of deforestation, interventions in the agriculture sector could reduce deforestation emissions as well as reduce emissions in the agriculture sector. Our study uses a novel approach to quantify agriculture-driven deforestation and associated emissions in the tropics between 2000 and 2010. Emissions from agriculture-driven deforestation in the tropics (97 countries) are 4.3 GtCO2e yr−1. We investigate the national potential to mitigate these emissions through forest land-sparing interventions, which can potentially be implemented under REDD+. We consider intensification and utilization of available non-forested land as forest land-sparing opportunities since they avoid the expansion of agriculture into forested land. In addition, we assess the potential to reduce agricultural emissions on existing agriculture land. The use of a systematic framework demonstrates the selection of mitigation interventions by considering sequentially the level of emissions, mitigation potential of various interventions, enabling environment and associated risks to livelihoods at the national level. Our results show that considering only countries with high emissions from agriculture-driven deforestation, with potential for forest-sparing interventions and a good enabling environment (e.g. effective governance or engagement in REDD+), there is a potential to mitigate 1.3 GtCO2e yr−1 (20 countries of 78 with sufficient data). For countries where we identify agricultural emissions as a priority for mitigation, up to 1 GtCO2e yr−1 could be reduced from the agriculture sector including livestock. Risks to livelihoods from implementing interventions based on national level data call for detailed investigation at the local level to inform decisions on mitigation interventions. Three case studies demonstrate the use of the analytical framework. The inherent link between the agriculture and forestry sectors due to competition for land suggests that these sectors cannot be considered independently. Our findings highlight the need to include the forest and the agricultural sectors in the decision-making process to mitigate deforestation.